Exploration on the understanding of organ donation activities among Muslims in Kuantan - Mohamad Ismail, Mohamad Firdaus; Roslan, Muhammad Firdaus; Shahadan, Siti Zuhaidah (IIUM Press, 2022)
Introduction: A common treatment for patients nearing the end of their life expectancy is organ donation and transplantation. Organ donation can cure diseases and save the lives of those who need them. End-stage organ failure patients must have an organ transplant in order to survive and return to a normal life. The most common obstacle to organ donation is finding a donor willing to save other people's lives. Muslims are less likely to donate organs because of a lack of understanding of organ donation activities. To devise a strategy, it is necessary to gain a better understanding of organ donation activities. The purpose of this study is to examine the perceptions of Kuantan's Muslim population regarding organ donation. Methodology: Based on interviews, this study employs a qualitative approach. An in-depth interview was conducted with eight residents of Kuantan, Pahang, in a semi-structured manner. There was a thematic analysis of the data. Results: Among the topics discussed were understanding organ donation, decision-making factors, the current updates related to organ donation activities in Malaysia, awareness of Islamic guidelines related to organ donation, and a source of information. Conclusion: Due to misunderstanding and anxiety, the willingness to register as a donor is still lacking. As a result of awareness campaigns, family and friends can all positively influence organ donation. The Islamic view on organ donation should be conveyed to the public in an easy-to-understand manner by religious leaders.